The Observed and Simulated Major Summer Climate Features in Northwest China and Their Sensitivity to Land Surface Processes - 李倩 薛永康 (Acta meteorologica Sinica, 2014)
Northwest China （NWC） is a typical arid and semi-arid region. In this study, the main summer climate features over NWC are presented and the performance of an atmospheric general circulation model （NCEP GCM/SSiB） over this region is evaluated. Satellite-derived vegetation products are applied in the model. Based on comparison with observational data and Reanalysis II data, the model generally captures major features of the NWC summer energy balance and circulation. These features include： a high surface tem- perature center dominating the planetary boundary layer; widespread descending motion; an anticyclone （cyclone） located in the lower and middle （upper） troposphere, covering most parts of central NWC; and the precipitation located mainly in the high elevation areas surrounding NWC. The sensitivity of the summer energy balance and circulation over NWC and surrounding regions to land surface processes is assessed with specified land cover change. In the sensitivity experiment, the degradation over most parts of NWC, except the Taklimakan desert, decreases the surface-absorbed radiation and leads to weaker surface thermal effects. In northern Xinjiang and surrounding regions, less latent heating causes stronger anomalous lower-level anticyclonic circulation and upper-level cyclonic circulation, leading to less summer precipitation and higher surface temperature. Meanwhile, the dry conditions in the Hexi Corridor produce less change in the latent heat flux. The circulation change to the north of this area plays a domi- nant role in indirectly changing lower-level cyclonic conditions, producing more convergence, weaker vertical descending motion, and thus an increase in the precipitation over this region.